2020
DOI: 10.35848/1347-4065/ab7355
|View full text |Cite
|
Sign up to set email alerts
|

Frequency increase in resonant-tunneling diode cavity-type terahertz oscillator by simulation-based structure optimization

Abstract: Terahertz (THz) radiation, in the range between the light waves and millimeter waves, has gained much attention because of its various promising applications. Resonant tunneling diodes (RTDs) have the potential for use as compact and coherent THz sources operating at room temperature. In this paper, oscillation frequency limitations and structure dependences for a RTD THz oscillator with a cylindrical cavity resonator are analyzed. Based on the dependences of the oscillation frequency on resonant cavity dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…As the RTD output powers and available oscillation frequencies progressively improve with ongoing research, we anticipate that the range of applications will widen, in a way that might parallel the history of devices such as the light-emitting diode. Currently, RTD oscillation frequencies up to 1.98 THz are demonstrated [ 17 ], although simulations show it could reach even higher, to about 3 THz [ 18 ]. The output power is now in the microwatt order, but an incoherent array of RTDs was shown to emit 0.73 mW [ 19 ] and research is ongoing toward a single-element power emission of several milliwatts [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the RTD output powers and available oscillation frequencies progressively improve with ongoing research, we anticipate that the range of applications will widen, in a way that might parallel the history of devices such as the light-emitting diode. Currently, RTD oscillation frequencies up to 1.98 THz are demonstrated [ 17 ], although simulations show it could reach even higher, to about 3 THz [ 18 ]. The output power is now in the microwatt order, but an incoherent array of RTDs was shown to emit 0.73 mW [ 19 ] and research is ongoing toward a single-element power emission of several milliwatts [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the surface area of the cavity is large, the conduction loss is small and high-frequency oscillation is expected. A theoretical calculation [ 34 ] has shown that oscillation up to approximately 2.8 THz is possible by optimizing the radius and height of the cylindrical cavity, as shown in Figure 6 b. In a preliminary experiment, 1.78 THz oscillation has been obtained for a non-optimized structure with parasitic capacitance [ 33 ].…”
Section: Novel Oscillator Structures For High Frequency High Outpmentioning
confidence: 99%
“… RTD oscillator integrated with cylindrical cavity and bow-tie antenna for high-frequency oscillation [ 33 , 34 ]: ( a ) Oscillator structure, and ( b ) calculation of oscillation frequency as a function of cavity height and radius. Copyright (2020) The Japan Society of Applied Physics [ 34 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The RTD oscillator is an electrical device with fundamental oscillation frequency in the terahertz frequency range at room temperature [16]. Oscillation from the sub-terahertz to 1.98 THz range has been achieved [17][18] [19][20] [21], and oscillation up to 2.77 THz is expected [22]. A single oscillator can be fabricated on a millimeter-sized chip [23].…”
Section: Introductionmentioning
confidence: 99%